Confronting a Global Pandemic: Responses from Caribb ean Extension Service Providers - Jeanelle Joseph; Tessa Barry (Journal of International Agricultural and Extension Education, 2021)
Agricultural Extension is an essential service, and this was even more so highlighted in this global pandemic which has significantly affected the agricultural sector. This rapid research sought to assess the capacity of Caribbean extension and advisory service providers. Seventy extension service providers from 11 Caribbean countries responded to an open-ended questionnaire administered via the Survey Monkey platform. The findings indicated that governments played an important role in providingopportunities such as distribution of seedlings to encourage producers,and promoted backyard gardening and other programmes to ensure continuity of country’s food security. Extension officers faced a number of barriers in the execution of their duties. Some of the barriers included technologicalbarriers, limited resources, and limited mobility as a result of the necessary restrictions and in some cases psychological barriers such as the fear of contracting the disease in the execution of their duties. Officers however utilized strategies such asincreased use of ICTs to train farmers and link them to market opportunities. In an attempt to increase the use of ICTs a number of challenges were highlighted. Challenges such as limited ICT resources for officers, poor connectivity in some remote areas,aged farmers literacy levels in the use of ICTs as well as access. This rapid research recommends policy development towards the increased use of e-extension with consultation among key stakeholders. This can be done on a regional basis, and eventually scaled up in an effort to further strengthen extension and advisory services globally
Keywords: agricultural extension; Caribbean region; Extension and Advisory Services (EAS); ICTs; knowledge manageme agricultural extension; knowledge management